Treatment with Tranexamic Acid during Pregnancy, and the Risk of Thrombo-Embolic Complications - Lindoff, Claes; Rybo, Göran; Åstedt, Birger (Thrombosis and Haemostasis, 1993)
Tranexamic acid (AMCA) is an inhibitor of fibrinolysis used to treat fibrinolytic bleeding (e.g., menorrhagia and gastro-intestinal haemorrhage), and to prevent bleeding at surgery, in cases of abruptio placentae and general haemorrhage. As AMCA stabilises preformed clots and prolongs their dissolution, it has been debated whether treatment with AMCA might predispose to thrombosis by depressing the fibrinolytic system. Pregnant women constitute a group with low fibrinolytic capacity and an increased frequency of thrombosis further increased after Caesarean section, and are thus more likely to be susceptible to antifibrinolytic therapy. We therefore carried out a retrospective analysis of the case records of 2,102 patients with various bleeding disorders during pregnancy. Of the 256 patients treated with AMCA (mean duration of treatment, 46 days), 169 were delivered by Caesarean section. Of the remaining 1,846 patients (i.e., controls), 443 were delivered by Caesarean section. The relationship between the use of AMCA and the occurrence of thrombo-embolism was calculated with 95% confidence limits.Of the AMCA treated group (n = 256), two patients – one of whom belonged to the Caesarean section subgroup (n = 168) – had pulmonary embolism. Of the controls (n = 1,846), three patients had deep vein thrombosis and one had pulmonary embolism, all four cases belonging to the Caesarean section subgroup (n = 443). Thus, the findings in this high risk group of women with complicated pregnancies, frequently entailing delivery by Caesarean section, provided no evidence of any thrombogenic effect of AMCA.